Historical geography of the silk road (Journal of Geography and Environmental Management, 2021)
The "Silk Road" is an international channel for human trade and cultural exchanges that spans the Eurasian continent and lasts for more than two thousand years. It has contributed to the social and economic development and cultural exchanges of Asian and European countries, especially ancient China. A huge contribution, it is like a geographical artery that flows the blood of human culture. The discovery of the Silk Road was a great initiative in the history of human civilization, and it was the longest international transport route between the East and the West in ancient times. This international transport route served as a bridge for political, economic and cultural communication among the countries along the Silk Road and facilitated the spread and exchange between the ancient Indian, Egyptian, Greek and Chinese civilizations. Throughout history, we can conclude that the Silk Road emerged in tandem with the opening of China. The prosperous period of the Silk Road was a period of great openness in Chinese history, as China's openness waned, the Silk Road gradually declined, and the Middle Ming Dynasty "closed" after interregional exchanges along the Silk Road largely stalled. With China's increasing openness in the 21st century, the Silk Road has experienced a renaissance.
Keywords: Silk Road, Emperor Wu of the Han Dynasty, Zhang Qian, Ban Chao, Western Regions.